Slow evaporation technique to grow 3 – Amino benzene sulfonic acid single crystal for Non-Linear optical (NLO) transmission. (2022) - Deepa, B.; Gayathiridevi, K.; Kalyan Chakravarthi, M.; Shajahan, A.; Shanti Sree, B; Imran Anees, Mohammed; Habeeb, Mohammad
Abstract: Crystal 3 Amino benzene sulfonic acid single crystal was grown using a slow evaporation process. The functional groups contained in the substances are identified via FT-IR analysis. X-ray diffraction investigation gives type of crystal. The dielectric behaviour of generated crystal was investigated at various frequencies and temperatures. The Kurtz powder second harmonic generation exhibits material behaviour of second harmonic generation and has an efficiency of 0.55 times that of KDP, making it ideally suited for non-linear optical (NLO) transmission.